1989
DOI: 10.1177/37.7.2567299
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody against human kidney gamma-glutamyl transpeptidase: preparation, immunochemical, and immunohistochemical characterization.

Abstract: To perform immunohistochemical study of the distribution of gamma-glutamyl transpeptidase in human organs, a highly specific antibody against the human enzyme is required. We prepared monoclonal antibody against gamma-glutamyl transpeptidase from human kidney, using the hybridoma technique. The antibody was of the IgG1 type and the light chain belonged to the kappa class. The antibody reacted specifically with the 63 KD heavy subunit of the enzyme. Examination of the specificity of the antibody performed by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Detection of high levels of GGT in the proximal tubules of the kidney by the GGT129 antibody is in agreement with previous studies of GGT expression in humans and rodents (Shiozawa et al, 1989;Rutenburg et al, 1969;Albert et al, 1964). In the kidney, GGT initiates the cleavage of glutathione into three amino acids which can then be reabsorbed from the glomerular filtrate.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Detection of high levels of GGT in the proximal tubules of the kidney by the GGT129 antibody is in agreement with previous studies of GGT expression in humans and rodents (Shiozawa et al, 1989;Rutenburg et al, 1969;Albert et al, 1964). In the kidney, GGT initiates the cleavage of glutathione into three amino acids which can then be reabsorbed from the glomerular filtrate.…”
Section: Discussionsupporting
confidence: 80%
“…A Western blot of homogenates of five human tissues showed that the affinity-purified antibody reacted with a single band corresponding to the large subunit of GGT (Shiozawa et al, 1989;Bte and Galbraith, 1987). The amount of GGT heavy subunit detected on the Western blot correlated with the relative level of GGT activity determined biochemically and by immunohistochemical staining of the corresponding tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aminopeptidases A and M or angiotensinase A and dipeptidyl peptidase lv. which form a major group of cell-membrane-bound proteins in the renal tubular brush border [11,14].…”
Section: Discussionmentioning
confidence: 99%
“…The method of MAb production has been described previously (38,45). In short, 6-week-old female Balb/c mice were subcutaneously immunized with the secretory granule membrane (100 pg protein) with complete Freund's adjuvant, and with incomplete Freund's adjuvant 2 weeks later.…”
Section: Preparation Of Ma6mentioning
confidence: 99%